Evaluation of heavy metal pollution risk associated with road sediment - Newaz, K.K.; Pal, S.K.; Hossain, S.; Karim, A. (Korean Society of Environmental Engineers, 2021)
A detailed investigation has been conducted to assess the heavy metal pollution risk associated with the road deposited sediment collected from the 32 major road sites in Chittagong city. The acid digestion of road sediments for metals extraction was carried out prior to determine total concentrations of Zn, Pb, Cr, Cu, Ni, Cd by using Polarized Zeeman Atomic Absorption Spectrophotometer (Z-2000) following standard analytical protocol. The contamination and pollution risk level were assessed using degree of contamination, potential ecological risk index and integrated pollution index. The study revealed that the mean heavy metal concentrations of Zn, Pb, Cr, Cu, Ni, Cd were found as 975, 84, 77, 74, 32, 1.6 mg/kg, respectively, across the road sites in Chittagong city. The mean concentrations are found 1.1 to 44 times higher in comparison to soil background, signifying relatively greater enrichment for Zn, Cd and Pb across the sites, suggesting vehicular emission on roads with site-specific characteristics. Based on pollution indices, Ruby Cement, City Gate and Enayeth Bazar road sites pose high risk, while eight other sites are found with moderate to considerable risk potential, and remaining 21 sites pose low to moderate risk potential.